Analysis of Drop Sensor Accuracy in Central Infusion Peristaltic Monitoring Based on Computer Using Wireless Communication HC-11 - Syaifudin Syaifudin; Triana Rahmawati; Siti Rohmatul Jannah; Sandeep Kumar Gupta; Ram Gopal (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
In some hospitals, the infusion is still done manually, where medical personnel observe the liquid droplets directly and then control the rate using a mechanical resistor (clamp). This method is certainly far from accurate. An infusion pump is a medical aid that functions to control and ensure the correct dose of infusion fluid given to patients treated. The purpose of this study was to analyze the accuracy of the infrared photodiode as a drop sensor based on the readings of the infusion pump monitoring system. This module consists of a photodiode infrared drop sensor module, a comparator circuit, a monostable circuit, a stepper motor, an L298N motor driver, and an ATmega328 microcontroller. The droplets were detected by an infrared photodiode sensor, then compared with a comparator and monostable circuit as an oscillator developer, and then the flow rate and residual volume readings were generated by the ATmega328 microcontroller. Next, this data has sent to the computer via the HC-11 wireless. The results of the flowrate module measurement show the highest error value of 3% at the 30 ml/hour setting and the lowest error value of 2.5% at the 60 ml/hour setting. Meanwhile, the results of the flow rate measurement using an infusion device analyzer obtained the highest error value of 4% at the setting of 30 ml/hour and 60 ml/hour, and the lowest error value of 0.8% at the setting of 100 ml/hour. Monitoring the infusion pump was designed centrally to facilitate the nurse's task in monitoring the infusion dose given to the patient accurately. Based on this research, the accuracy of the infrared sensor and photodiode is very good by looking at the existing error rate.